Broadly cross-reactive immune responses in chickens immunized with chimeric virus-like particles of nodavirus displaying the M2e originated from avian and human influenza A viruses - Thian, Bernard Yi Zhe; Mohd Nasir, Nurul Fatimah; Wong, Chuan Loo; Ong, Hui Kian; Abdul Razak, Mariatulqabtiah; Ho, Kok Lian; Omar, Abdul Rahman; Tan, Wen Siang (Elsevier Ltd, 2025)
Avian influenza A viruses (IAVs) pose a persistent threat to poultry industry worldwide, despite the presence of vaccines. Additionally, reverse-zoonosis transmission potentially introduces human-originated IAVs into poultry and complicates the efforts to control the spread of influenza. Current avian influenza vaccines are primarily based upon the rapidly mutating hemagglutinin (HA) and neuraminidase (NA) glycoproteins, which limit their efficacy against diverse strains of IAVs. Hence, the highly conserved ectodomains of matrix 2 protein (M2e) of IAVs are widely studied as alternatives to the HA and NA. However, the differences in the M2e amino acid sequences between avian and human IAVs generate antibodies that do not cross-react reciprocally with IAVs from other origins. To broaden and enhance the immunogenicity of M2e, we fused two copies each of the M2e derived from avian and human IAVs at the C-terminal end of the Macrobrachium rosenbergii nodavirus (MrNV) capsid protein (NvC). Transmission electron microscopic and dynamic light scattering analyses revealed that the chimeric protein self-assembled into virus-like particles (VLPs). Immunization of chickens with the chimeric VLPs demonstrated a robust induction of broadly reactive immune responses against both the M2e of avian and human IAVs. Additionally, the chimeric VLPs elicited the production of cytotoxic T lymphocytes (CTL), macrophages, as well as a well-balanced Th1 and Th2 population, indicating their potential in activating cell-mediated immune responses in chickens. Furthermore, the chimeric VLPs triggered the production of both Th1- and Th2-cytokines, attesting their potential in mounting a robust and balanced immune response in avian species. This study demonstrated the potential of these chimeric VLPs in stimulating and broadening cross-reactive immune responses in chickens against both avian and human IAVs.